"We need a new story to guide us": Towards a curriculum of Rahma. Issue 2 (17th June 2021) - Saleh, Muna
Abstract: Beginning with a storied moment of encounter at an academic conference in which several scholars confidently asserted the need to "humanize those who have been dehumanized", I engage in autobiographical narrative inquiry into my tensions with this seemingly "common sense" pedagogical belief and curricular approach. I do so by interweaving my stories of experiences as a teacher educator, intergenerational survivor of Palestinian displacement, mother to a dis/abled child, and Canadian Muslim woman in hijab who is all too familiar with a condescending pity of those who project their stories of me—of who they believe me to be and what they believe my experiences to be—upon me. I also draw upon the work and ideas of curriculum, feminist, and cultural scholars and theorists to illuminate how teaching for the humanization of Others can impose borders within and between relational selves in the making. I invite other teacher educators and teachers—including those from within familial curriculum-making worlds—to imagine how we might co-compose what I have come to understand as a curriculum of Rahma alongside children, youth, families, caregivers, colleagues, and others within and across the many places we co-compose curriculum.